2018
DOI: 10.1111/eth.12806
|View full text |Cite
|
Sign up to set email alerts
|

Attraction and vibration: Effects of previous exposure and type of food resource in the perception of allocolonial odors in termites

Abstract: Social insects have an efficient recognition system that guarantees social cohesion and protection against intruders in their colonies and territories. However, the energy costs in constant conflicts with neighboring colonies could promote a reduction in the fitness of colonies. Here, we evaluated the effect of previous exposure to allocolonial odor and the consumption of similar food resources on aggressive behavior and choice of allocolonial cues in Nasutitermes aff. coxipoensis (Termitidae: Nasutitermitinae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…A range of studies have been shown the ability of animals to use social information to obtain benefits, such as access to food resources or information about local risk (i.e., presence of predators and competitors) (reviewed by Valone, 2007). For termites, the use of social information through chemical cues to obtain benefits has already been shown for inquiline species that coexist with host colonies (Cristaldo et al., 2014, 2016), among neighboring colonies from the same species (Cristaldo, Araújo, et al, 2016), and to have access to the presence of competitors (Evans et al., 2009; Ferreira, Cristaldo, et al, 2018). However, to the best of our knowledge, no study had investigated the use of social information during decision‐making in the resource selection by termite species.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…A range of studies have been shown the ability of animals to use social information to obtain benefits, such as access to food resources or information about local risk (i.e., presence of predators and competitors) (reviewed by Valone, 2007). For termites, the use of social information through chemical cues to obtain benefits has already been shown for inquiline species that coexist with host colonies (Cristaldo et al., 2014, 2016), among neighboring colonies from the same species (Cristaldo, Araújo, et al, 2016), and to have access to the presence of competitors (Evans et al., 2009; Ferreira, Cristaldo, et al, 2018). However, to the best of our knowledge, no study had investigated the use of social information during decision‐making in the resource selection by termite species.…”
Section: Discussionmentioning
confidence: 98%
“…coxipoensis that use similar food resources increased alertness via a greater number of vibration than individuals who consumed different food resources. Additionally, the aggressiveness between neighbors of intraspecific colonies is more intense under low‐resource offer situation (Ferreira, Cristaldo, et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the individuals of N. aff. coxipoensis are attracted to allocolonial odor cues to which they were previously exposed (Ferreira et al, 2018).…”
Section: Interspecific Interaction Via Termite Pheromonesmentioning
confidence: 99%
“…Since the diet of the inquiline consists of feces of the host impregnated on the inner wall of the nest (Barbosa-Silva et al 2016), the constitution of odors between the host and inquiline could, in part, be similar. Studies performed with other termite species have shown that the use of a similar diet can promote two opposite patterns: less aggressivity through similarity in the composition of cuticular hydrocarbons (Florane et al 2004), or greater issuing of alarms (e.g., vibration), which could promote evasion of the location (Ferreira et al 2018). In addition, studies have found habituation of signals between different termite colonies maintained in close contact ).…”
Section: Introductionmentioning
confidence: 99%